Islah of al-Ghazali’s ideas and movements and their relevance to contemporary Islamic preaching - Azwar; Abur Hamdi Usman; Umar Muhammad Noor; Mohd Farid Ravi Abdullah (ResearchGate, 2024)
This study aims to examine the thoughts, movements of iṣlāḥ (reform) and tajdīd (renewal) of Abū Ḥāmid al-Ghazālī (d. 1111) and their relevance to the contemporary da‘wah. Based on a descriptively qualitative method and socio-historical approaches, this study shows that Al-Ghazālī prioritized self-reform before societal engagement. AlGhazālī emphasized Muslims’ mission to spread Islam and reform society. He identified societal issues, attributing the state of society to the knowledge and credibility of Islamic scholars, and advocated for nurturing new scholars, reforming education, reviving moral values, and promoting social justice. Furthermore, his ideas influenced the emergence of leaders like Ṣalāḥ al-Dīn al-Ayyūbī through educational reforms. In the contemporary context, al-Ghazālī’s thought and movement provide an understanding that the current problems of Muslims need to be resolved from a fundamental problem in the form of ‚moral reform‛. The roles of ‘ulamā’ (scholars) and umarā’ (leaders) are two essential pillars of the ummah (community), and these two aspects must receive necessary attention in Islamic da‘wah.